2019
DOI: 10.15386/mpr-1375
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus reuteri versus triple therapy for the eradication of Helicobacter Pylori in functional dyspepsia

Abstract: Background and aimThe eradication of H. pylori infection using PPI associated with different combinations of two or three antibiotics entails high risks of side effects and non- adherence. Therefore probiotics have been proposed for H. pylori eradication.We tested the efficacy of Lactobacillus reuteri plus Pantoprazole compared to a triple regimen based on Pantoprazole plus Amoxicillin plus Clarithromycin in patients with H. pylori infection and functional dyspepsia.MethodsIn a prospective design, 46 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…The symptoms of satiety, bloating, pain, and anxiety score changes in the two groups had no statistical significance. L. reuteri may be a good alternative to antibiotics, and it can be used to eradicate H. pylori infection in patients with chronic dyspepsia (Muresan et al 2019). However, Dore et al studied that the cure rate of taking PPI with Lactobacillus reuterii instead of antibiotics or bismuth was 12% (Dore et al 2019a).…”
Section: Probiotics With Ppimentioning
confidence: 99%
“…The symptoms of satiety, bloating, pain, and anxiety score changes in the two groups had no statistical significance. L. reuteri may be a good alternative to antibiotics, and it can be used to eradicate H. pylori infection in patients with chronic dyspepsia (Muresan et al 2019). However, Dore et al studied that the cure rate of taking PPI with Lactobacillus reuterii instead of antibiotics or bismuth was 12% (Dore et al 2019a).…”
Section: Probiotics With Ppimentioning
confidence: 99%
“…This L. reuteri strain was shown to significantly decrease the HP bacterial load in infected adults in two weeks, suggesting that it might be used as an adhesion blocker in anti-HP therapies [ 41 ]. In a randomized trial in 46 patients, Muresan et al showed that triple therapy with Pantoprazole for 30 days associated with Amoxicillin, and Clarithromycin for 14 days, was comparable with a regimen of Pantoprazole plus L. reuteri DSMZ 17648 twice a day for 8 weeks with a better trend in favor of the antibiotic group as compared to the probiotic group (74% vs. 65%, respectively) [ 42 ]. Buckley et al concluded that L. reuteri DSM 17648 reduces H. pylori load, improving gastrointestinal symptoms in subjects positive to this infection, and improving antibiotic–gastrointestinal adverse effects that are common after eradication treatment with antibiotics [ 43 ].…”
Section: Use Of Different Strains Rather Than L Reuteri 17938 Against Hp Infection Without Antibioticsmentioning
confidence: 99%
“…However, these results are based on a small number of patients with FD (n = 20) (Table 1). A more recent study 47 has investigated the efficacy of L. reuteri DSMZ 17648 (Pylopass, Remedia Laboratories, Romania) twice a day plus pantoprazole 40 mg bid for 8 weeks versus triple therapy (pantoprazole 40 mg bid 30 days, amoxicillin 1000 mg bid 14 days, and clarithromycin 500 mg bid 14 days) in FD patients Hp positive. Results support the use of probiotics since eradication of Hp was associated with improvement of dyspeptic symptoms and anxiety score in both subgroups.…”
Section: Clinical Trials That Used Probiotics In Patients With Fdmentioning
confidence: 99%